Penyuluhan Pemadanan NPWP dengan NIK: Langkah Efektif Menuju Administrasi Pajak yang Terpadu - Lenny Panggabean; Milko Hutabarat; Jisman M. Lubis; Rudy S. Sinaga; Swanto Sirait; Greis Klara Harianja; Tabhita Regina Maanary; Lerina Mariska Butar Butar; Priskila F. Damar (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2024)
The outreach on matching Individual Taxpayer Numbers (NPWP) with Population Identification Numbers (NIK) is a crucial effort to enhance tax administration efficiency and tax compliance in Indonesia. NPWP and NIK are two significant identifiers for Indonesian citizens, but discrepancies or data duplication between them are common. Faculty from the Tax Management program, assisted by student volunteers from the tax volunteer group, conducted this matching activity through outreach to the community at the Christian University of Indonesia (UKI). They utilised questionnaires to gather feedback from participants on the topic discussed.The conclusion drawn is that the twenty-five participants who attended the outreach (PkM) are now aware of the necessity to match their NIK with NPWP. The final deadline for this matching is June 30, 2024, with full implementation to be enforced nationwide starting July 1, 2024. Participants expressed their satisfaction with the outreach conducted by the Tax Management faculty from the Vocational Faculty of UKI, with support from the tax volunteers.